Advances in Gut Microbiome Research, Opening New Strategies to Cope with a Western Lifestyle - Rodriguez-Castaño, Gina P.; Caro-Quintero, Alejandro; Reyes, Alejandro; Lizcano, Fernando (Frontiers in Genetics, 2017)
The 'westernization' of global eating and lifestyle habits is associated with the growing rate of chronic diseases, mainly cardiovascular diseases, cancer, type 2 diabetes mellitus, and respiratory diseases. The primary prevention approach is to make nutritional and behavioral changes, however, there is another important determinant of our health that only recently has been considered and is the presence of beneficial microorganisms and their products in our gastrointestinal tract. Microorganisms living in our body can alter the fate of food, drugs, hormones, and xenobiotics, and recent studies point to the use of microorganisms that can counteract the harmful effects of certain compounds introduced or produced endogenously in our body. This review considers the effects of the western lifestyle on adiposity, glucose metabolism, oxidative markers and inflammation profile, emphasizes on the studies that have investigated bacterial strains and products of their metabolism that are beneficial under this lifestyle, and examines the screening strategies that recent studies are using to select the most promising probiotic isolates. In addition, we consider the relevance of studying the microbiota of metabolically healthy people under a western lifestyle for the understanding of the key components that delay the development of chronic diseases.